FIGURE 3. A in Generic reclassification of species formerly included in Rhantus Dejean (Coleoptera, Dytiscidae, Colymbetinae) - Balke, Michael; Hájek, Jiří; Hendrich, Lars (Zenodo, 2017)
FIGURE 3. A) Carabdytes upin upin (Balke, Hendrich & Wewalka, 1992), 12 mm, Papua New Guinea; B) Meridiorhantus antarcticus (Germain, 1854), 14 mm, Chile; C) Meridiorhantus calidus (Fabricius, 1792), 13 mm, Chile; D) Meridiorhantus validus (Sharp, 1882), 13 mm, Chile. Published as part of Balke, Michael, Hájek, Jiří & Hendrich, Lars, 2017, Generic reclassification of species formerly included in Rhantus Dejean (Coleoptera, Dytiscidae, Colymbetinae), pp. 91-100 in Zootaxa 4258 (1) on page 95, DOI:10.11646/zootaxa.4258.1.7, http://zenodo.org/record/569186